Deaf and non-deaf basketball and volleyball players' multi-faceted difference on repeated counter movement jump performances: Height, force and acceleration - Soslu, Recep; Özer, Ömer; Uysal, Abdullah; Pamuk, Ömer (Frontiers in Sports and Active Living, 2022)
The aim of this study was planned to determine the multi-faceted difference between deaf/non-deaf athletes' Repeated Counter Movement Jump performances (basketball/volleyball). Athletes playing in the Turkish Deaf Basketball and Volleyball national teams and in Basketball and Volleyball First Leagues participated in the study. The study group consisted of 51 male athletes, including deaf basketball (n=11; height, body weight, age: 183.55±10.51 cm, 83.89±9.09 kg, and 26.18±4.79 years, respectively), deaf volleyball (n=12, height, body weight, age: 187.00±7.07 cm, 80.47±9.44 kg, and 26.33±4.27 years, respectively), non-deaf basketball (n=14, height, body weight, age: 196.93±9.14 cm, 94.34±8.60 kg, and 26.93±4.87 years, respectively), and non-deaf volleyball (n=14, height, body weight, age: 194.5±5.02 cm, 86.27±8.64 kg, and 24.93±5.10 years, respectively) players. As a result of the test, Jump Height from Take Off Velocity, Jump Height from Take Off Velocity, Jump Height from Flight Time, Counter Movement Acceleration, Push Off Acceleration, Average Velocity, Average Power and Average Force were analyzed. The data were normally distributed, the Paired Sample T-Test was carried out to compare differences in the mean values between the deaf basketball and volleyball, basketball and volleyball groups. As a result, this is the first study to investigate the number of jumps and jump height, the force produced, acceleration at the time of jump, and jump velocity during 30 seconds in deaf and non-deaf basketball and volleyball players within the scope of individual RCMJ test. Trainers and other practitioners should consider measuring their athletes' performances before training or applying repetitive CMJ exercises in training to adjust the number of jumps and jump heights, the force produced, the acceleration at the time of jump, and jump velocity more effectively.